Partial Identification of Economic Mobility: With an Application to the United States - Daniel L. Millimet; Hao Li; Punarjit Roychowdhury (Institute of Labor Economics (IZA), 2019)
The economic mobility of individuals and households is of fundamental interest. While many measures of economic mobility exist, reliance on transition matrices remains pervasive due to simplicity and ease of interpretation. However, estimation of transition matrices is complicated by the well-acknowledged problem of measurement error in self-reported and even administrative data. Existing methods of addressing measurement error are complex, rely on numerous strong assumptions, and often require data from more than two periods. In this paper, we investigate what can be learned about economic mobility as measured via transition matrices while formally accounting for measurement error in a reasonably trans- parent manner. To do so, we develop a nonparametric partial identification approach to bound transition probabilities under various assumptions on the measurement error and mobility processes. This approach is applied to panel data from the United States to explore short-run mobility before and after the Great Recession.
Keywords: C18; D31; I32; 330; partial identification; measurement error; mobility; transition matrices; poverty